Prevalence and associated factors of depressive and anxiety symptoms among healthcare workers in the post-pandemic era of COVID-19 at a tertiary hospital in Shenzhen, China: A cross-sectional study - Liang, Zhiya; Wang, Ying; Wei, Xiaoyue; Wen, Wanyi; Ma, Jianping; Wu, Jun; Huang, Shaofen; Qin, Pei (Frontiers in Public Health, 2023)
Background: Healthcare workers were at high risk of psychological problems during the COVID-19 pandemic, but it remains not well investigated in the post-pandemic era of COVID-19, with regular epidemic prevention and control embedded in burdened healthcare work. This study aimed to investigate the prevalence and potential risk factors of the symptoms of depression and anxiety among healthcare workers at a tertiary hospital in Shenzhen. Method: Our cross-sectional study was conducted among 21- to 64-year-old healthcare workers in December 2021 at a tertiary hospital in Shenzhen, using a simple random sampling strategy. A wide range of socio-demographic characteristics, individual information, and psychological condition of the subjects were extracted. Healthcare workers’ psychological conditions were tested with the Center for Epidemiologic Studies Depression (CESD-10), General Anxiety Disorder (GAD-7), Insomnia Severity Index (ISI), Work-Family Conflict Scale (WFCS), 10-item Connor-Davidson Resilience Scale (CD-RISC-10), and 17-item of Maslach's Burnout Inventory - Human Services Survey (MBI-HSS-17). Data were collected based on these questionnaires. Descriptive statistics were used to assess the difference between healthcare workers with depressive and anxiety symptoms among different groups. Hierarchical logistic regression analyses were conducted to investigate the association between focused variables and mental health outcomes. Results: A total of 245 healthcare workers were enrolled. The proportion of depressive symptoms, anxiety symptoms and their co-occurrence were 34.7%, 59.6% and 33.1% respectively. Logistic regression showed that for the three outcomes, no history of receiving psychological help and self-rated good or higher health were protective factors, whereas more severe insomnia and job burnout were risk factors. Junior or lower job title and higher psychological resilience were related to a lower prevalence of depressive symptoms, while relatively longer working hours and larger work-family conflict were positively associated with the anxiety symptoms. Psychological resilience was inversely associated with the co-occurrence of depressive and anxiety symptoms. Conclusions: Our study revealed a high proportion of psychological problems and proved that several similar factors which were significant during the pandemic were also associated with the symptoms of depression and anxiety among healthcare workers in the post-pandemic era of COVID-19. These results provide scientific evidence for psychological interventions for healthcare workers.